Enhancement of Clot Lysis In Vitro and In Vivo with a Bispecific Monoclonal Antibody Directed against Human Fibrin and against Urokinase-Type Plasminogen Activator - Kurokawa, Tomofumi; Iwasa, Susumu; Kakinuma, Atsushi; Stassen, Jean-Marie; Lijnen, H Roger; Collen, Desire (Thrombosis and Haemostasis, 1991)
A hybrid hybridoma (FU1-74), secreting a bispecific monoclonal antibody (bs mAb), was obtained by fusion of a murine hybridoma secreting a monoclonal antibody (mAb) specific for human fibrin with a murine hybridoma secreting a mAb against urokinase-type plasminogen activator (u-PA). The bs mAb (MA-FU1-74), purified to homogeneity from mouse ascitic fluid, migrated as a single band with apparent Mr 150,000 on non-reduced SDS-PAGE and had an affinity for both human fibrin (Ka = 2 × 107 M–1) and for u-PA (Ka = 108 M–1) comparable to that of the mAbs obtained from the respective parental hybridomas. MA-FU1-74 did not influence the enzymatic activity of two-chain u-PA (tcu-PA) towards plasminogen or towards a chromogenic substrate. The complex of MA-FU1-74 with recombinant single chain u-PA (rscu-PA) or with tcu-PA (urokinase) enhanced the fibrinolytic potency of the plasminogen activator towards clotted human plasma 20-fold and 5-fold, respectively.In a hamster pulmonary embolism model, the rscu-PA/MA-FU1-74 complex had a 13- to 17-fold increased thrombolytic potency (percent lysis per mg/kg u-PA administered) relative to that of rscu-PA. The specific thrombolytic activity (percent lysis per εg/ml steady state plasma level of u-PA antigen) of the complex was, however, not significantly different from that of rscu-PA. The complex of rscu-PA with the parental anti-u-PA mAb (MA-UK1-3) had only a 2-fold enhanced thrombolytic potency relative to that of rscu-PA and had a 5-fold decreased specific thrombolytic activity. The plasma clearance rates of the complexes of rscu-PA with both MA-FU1-74 and MA-UK1-3 were about 10-fold lower than that of rscu-PA. In a rabbit jugular vein thrombosis model, the rscu-PA/MA-FU1-74 complex had a 4-fold enhanced thrombolytic potency, an unchanged specific thrombolytic activity and 20-fold reduced plasma clearance. In both animal models, the rscu-PA/MA-FUl-74 complex did not cause more extensive systemic activation of the fibrinolytic system than rscu-PA.It is concluded that the bispecific anti-fibrin/anti-u-PA mAb MA-FU1-74 targets u-PA to the fibrin clot, resulting in a significantly enhanced thrombolytic potency of the plasminogen activator.